Permafrost Wetlands Are Sources of Dissolved Iron and Dissolved Organic Carbon to the Amur-Mid Rivers in Summer - Tashiro, Y.; Yoh, M.; Shesterkin, V.P.; Shiraiwa, T.; Onishi, T.; Naito, D. (American Geophysical Union, 2023)
Dissolved iron (dFe) transported by the Amur River greatly contributes to phytoplankton growth in the Sea of Okhotsk. Nevertheless, there has been little research on the source of dFe to rivers, especially in the Amur-Mid Basin, which is situated in a sporadic permafrost area. In the Amur-Mid Basin, permafrost generally exists in wetlands in flat valleys, and these permafrost wetlands could be a source of dFe to rivers. To assess the importance of permafrost wetlands for dFe export, we conducted a local survey on land and soil characteristics of wetlands, and moreover analyzed the chemical composition (dFe, dissolved organic carbon [DOC], pH, and electrical conductivity [EC]) of 24 rivers with different watershed sizes in summer. As a result of local survey, the thickly accumulated peat soils in the permafrost wetland were almost saturated and rich in organic matter from the surface to a greater depth near the permafrost table. In addition, the coverage of such permafrost wetlands in watersheds showed significant positive correlations with dFe (r2 = 0.67, p = 1.7e−6) and DOC (r2 = 0.48, p = 1.8e−4) and a negative correlation with EC (r2 = 0.52, p = 7.7e−5). The dFe concentration was also correlated well with DOC concentration (r2 = 0.68, p = 7.3e−7) but not correlated with pH and watershed area. These findings are the first to indicate that permafrost wetlands in the Amur-Mid Basin considerably contribute to dFe and DOC export to rivers, and their coverage primarily determines riverine dFe and DOC concentrations in summer.